STRATEGI KOMUNIKASI POLITIK OPINION LEADER DALAM DIFUSI PROGRAM PEMBANGUNAN DAN PENGEMBANGAN LEMBAGA LOKAL DI PEDESAAN (Opinion Leader Political Communication Strategy in Diffusion Development Program and Development of Local Institutions in Rural) - Selly Oktarina; Sarwititi Sarwoprasodjo (Universitas Lambung Mangkurat, 2018)
ABSTRACT Politics has entered almost every level of society in urban and rural areas. Previously, rural people is very taboo with